Associations between fatty infiltration of rotator cuff muscles and tear size or location of rotator cuff tendon - Kajiyama, Shiro; Chiba, Ko; Aoki, Tatsunari; Sada, Kiyoshi; Sato, Shuntaro; Osaki, Makoto (Frontiers in Surgery, 2024)
Background: Fatty infiltration (FI) of rotator cuff muscles in patients with rotator cuff tears is an important imaging factor for determining surgical indications, but the associations between FI grade and the size or location of adjacent rotator cuff tears are not well-known. The primary purpose of this study was to determine whether tear size and location, especially for the SSc tendon, are associated with FI of adjacent rotator cuff muscles. The secondary purpose was to clarify which patient factors are associated with rotator cuff muscle FI in rotator cuff tear cases.Methods: This study examined 373 shoulders of 348 patients (264 males and 109 females; mean age 62.8 years) who had undergone arthroscopic rotator cuff surgery. The FI grades of the supraspinatus (SSP), infraspinatus (ISP), and subscapularis (SSc) muscles were assessed on preoperative magnetic resonance imaging (MRI) using the Goutallier classification modified by Fuchs. According to the preoperative MRI and intraoperative findings, the tear size of the posterior-superior rotator cuff (SSP-ISP) was classified using a modified six-grade scale of the Cofield classification, and that of the SSc tear was classified using a six-grade scale according to the Lafosse classification. Age at surgery, sex, body mass index (BMI), presence of diabetes mellitus (DM) or hyperlipidemia (HL), trauma history, and duration of symptoms were investigated.The FI grades of the SSP, ISP, and SSc were significantly associated with the size of the tears in those muscles (all P<0.01). Furthermore, the FI grades of the SSP and the ISP were significantly associated with SSc tear size (P<0.01), and the FI grade of the SSc was significantly associated with SSP-ISP tear size (P<0.01). Patient age at surgery was significantly associated with FI grade (P<0.01), with significant progression of the FI grade with advancing age, but there were no significant associations between the FI grade and sex, BMI, presence of DM or HL, trauma history, and duration of symptoms.